Political legitimacy and housing : stakeholding in Singapore - Chua, Beng Huat (Routledge, 1997)
Looking at the ways in which Singapore's planners have dealt with the problems of creating communities in a modern urban environment, the author concludes that the success of the public housing programme has done much for the nation.